IMPLEMENTASI TANDA TANGAN ELEKTRONIK PADA PELAYANAN METROLOGI LEGAL: STUDI PADA PELAYANAN TERA DAN TERA ULANG TANGKI UKUR MOBIL (TUM) DI UPT METROLOGI LEGAL KOTA PEKANBARU. - Herlina Vivianti; Sufian Sufian; Dia Meirina Suri; Eka Komalasari (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the implementation of Electronic Signatures (Tanda Tangan Elektronik/TTE) in the verification and re-verification services of Mobile Measuring Tanks (Tangki Ukur Mobil/TUM) at the Legal Metrology Unit of Pekanbaru City. The research employed a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, and analyzed using the Digital Era Governance framework proposed by Dunleavy et al. (2006), which includes the dimensions of reintegration, needs-based holism, and digitalization. The findings indicate that the implementation of electronic signatures has supported the transformation of legal metrology services toward a digital-based administrative system. The use of TTE has accelerated administrative processes, improved service efficiency, and ensured the security, authenticity, and integrity of electronic documents through digital authentication and verification mechanisms. However, its implementation has not been fully optimized. In the reintegration dimension, obstacles include transitions of authorized signatories, data input errors, and the lack of full integration in the issuance system of Testing Result Certificates (Surat Keterangan Hasil Pengujian/SKHP). In the digitalization dimension, challenges involve unstable internet connectivity, limited computer facilities, and the absence of backup power systems. Meanwhile, within the needs-based holism dimension, some service users still experience delays in receiving SKHP documents despite their electronic issuance. The study concludes that TTE implementation has contributed to digital transformation and enhanced document security in TUM verification services. Nevertheless, improvements in system integration, information technology infrastructure, and service governance are required to achieve more effective, efficient, secure, and user-oriented public services.